2016
DOI: 10.5195/jyd.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

“You gotta respect”: Mexican-origin Adolescents’ Perspectives on Respect in Organized Activities

Abstract: Respect is crucial for promoting participation and positive experiences in organized activities, especially among ethnically diverse youth. However, little is known regarding how Mexican-origin adolescents conceptualize respect and specifically how to promote respect in activities. Guided by theory and previous research, we used qualitative content analysis to elucidate perspectives on respect and features involved in the development of respect in activities. Our sample consisted of 18 Mexican-origin 7th grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Themes emerging across studies include the importance that Latinx youth place on positive relationships with adult staff and on experiencing the program as a “safe haven” (e.g., Diversi & Mecham, 2005; Lee, Borden, & Perkins, 2009). An analysis of Mexican-origin adolescents’ experiences in a range of programs, including sports, arts, clubs, and religious activities, revealed the importance they placed on programs valuing and celebrating youth’s cultural backgrounds (e.g., by respecting linguistic differences, helping youth learn about cultural similarities and differences; Ettekal, Gaskin, Lin, & Simpkins, 2015). In a multiethnic sample, only Latinx girls mentioned the opportunity to learn about cultures as a reason for program participation (Perkins et al, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Themes emerging across studies include the importance that Latinx youth place on positive relationships with adult staff and on experiencing the program as a “safe haven” (e.g., Diversi & Mecham, 2005; Lee, Borden, & Perkins, 2009). An analysis of Mexican-origin adolescents’ experiences in a range of programs, including sports, arts, clubs, and religious activities, revealed the importance they placed on programs valuing and celebrating youth’s cultural backgrounds (e.g., by respecting linguistic differences, helping youth learn about cultural similarities and differences; Ettekal, Gaskin, Lin, & Simpkins, 2015). In a multiethnic sample, only Latinx girls mentioned the opportunity to learn about cultures as a reason for program participation (Perkins et al, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, although some ethnic cultural features were not a priority, they still generated enthusiasm. For example, parents and adolescents enjoyed that same-ethnic peers provided opportunities to reinforce ethnic culture and that diverse peers fostered interethnic group respect (Ettekal, Gaskin, Lin, & Simpkins, 2015), but they also felt like they did not have a choice or were used to the absence of ethnic cultural features in their local activities. Thus, the contradiction may be the product of cognitive dissonance (Festinger, 1957), such that parents and adolescents with limited exposure to ethnic cultural features may have adjusted their preferences to align with what was available to them.…”
Section: Discussionmentioning
confidence: 99%
“…This complements prior work indicating that issues of culture and race arise spontaneously in the course of program activities or as a result of events outside the program (Gutiérrez, Larson, Raffaelli, Fernandez, & Guzman, 2017). Studies of Mexican-origin families have revealed the salience of cultural aspects, with some adolescents reporting being the targets of ethnic/racial microaggressions (e.g., ethnic name-calling and teasing) in the context of school-based sports activities (Lin et al, 2016) and others emphasizing the importance of respect for both cultural similarities and differences (Ettekal et al, 2016). The current findings indicate that parents also see culture is a salient dimension of their adolescents’ program experiences, bolstering the argument that to be effective, programs must be culturally responsive (Simpkins et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Latinx adolescents’ reports of opportunities for ethnic socialization in their after-school program were associated with increased ethnic identity 9 weeks later (Riggs, Bohnert, Guzman, & Davidson, 2010). Mexican-origin youth participating in programs reported that their cultural backgrounds should be valued and that programs should be a space where all youth could celebrate their culture (Ettekal, Gaskin, Lin, & Simpkins, 2016). Finally, a study of Latinx youth from four radio-training programs indicated they learned about the world and themselves through the diversity they encountered in the program (Huesca, 2014).…”
Section: Cultural Socialization and The Potential Role Of Organized Ymentioning
confidence: 99%